Perspectives in modeling and model validation during analytical quality by design chromatographic method evaluation: a case study - Yongzhi Dong; Zhimin Liu; Charles Li; Emily Pinter; Alan Potts; Tanya Tadey; William Weiser (SpringerOpen, 2021)
Abstract Design of experiments (DOE)-based analytical quality by design (AQbD) method evaluation, development, and validation is gaining momentum and has the potential to create robust chromatographic methods through deeper understanding and control of variability. In this paper, a case study is used to explore the pros, cons, and pitfalls of using various chromatographic responses as modeling targets during a DOE-based AQbD approach. The case study involves evaluation of a reverse phase gradient HPLC method by a modified circumscribed central composite (CCC) response surface DOE. Solid models were produced for most responses and their validation was assessed with graphical and numeric statistics as well as chromatographic mechanistic understanding. The five most relevant responses with valid models were selected for multiple responses method optimization and the final optimized method was chosen based on the Method Operable Design Region (MODR). The final method has a much larger MODR than the original method and is thus more robust. This study showcases how to use AQbD to gain deep method understanding and make informed decisions on method suitability. Discoveries and discussions in this case study may contribute to continuous improvement of AQbD chromatography practices in the pharmaceutical industry.